Dropping Draupadi: The Crisis of A Woman Translating A Woman - Ankita Bose (Litinfinite, 2022)
This academic essay seeks to criticize Delhi University’s exclusion of Bengali writer Mahasweta Devi’s Draupadi, translated into English by Gayatri Chakravorty Spivak, from its ‘women’s writing’ course in B.A. English (Honours) curriculum in August 2021. It attempts to establish the text as a crucial example of ‘a woman translating a woman’. In doing so, it evokes postructural feminism as the basis of the shared agenda between the writer and the translator, as the text is transmitted through the process of translation as “literary activism”. It seeks to argue how such an act of translation can subvert the existing status quo of the phallocentric and hypermasculine power relations of the nation-state through the site of a woman’s raped body—both as a site of oppression and resistance. It raises crucial questions on the politics that lurk behind the censoring of the text, throwing light upon the growing crisis of feminist translations today. In conclusion, it puts forward an urgent appeal to multiply the translation of a woman, and by a woman, so that such a crisis could be circumvented, if not subverted.